OSLERUS OSLERI (COBBOLD, 1876) INFECTION IN MANED WOLF (CHRYSOCYON BRACHYURUS, ILLIGER, 1815) - Dias, Rafael Groberio Souto [UNESP]; Legatti, Emerson [UNESP]; Rahal, Sheila Canevese [UNESP]; Teixeira, Carlos Roberto [UNESP]; Ruiz Junior, Raul Lopes [UNESP]; Rocha, Noeme Sousa [UNESP]; Santos, Ivan Felismino Charas dos [UNESP]; Schmidt, Elizabeth Moreira dos Santos [UNESP] (Amer Assoc Zoo Veterinarians, 2012)
Oslerus osleri is a small nematode that infects the respiratory tract of domestic and wild canids and is responsible for causing chronic nodular tracheobronchitis. This paper aims to report a case of parasitism by O. osleri in a free-living maned wolf (Chrysocyon brachyurus) that was struck by a motor vehicle. Fecal samples were collected, and the presence of spiral larvae, with S-shaped tails, was observed on flotation. This characteristic was compatible with the Filaroididae Family larvae of O. osleri. Although the animal did not show clinical signs of respiratory system impairment, a tracheobronchoscopy was performed. Semitransparent nodules, 5 mm in diameter, containing adult parasites were observed in the third distal portion of the trachea, cranial to the carina. Larval morphological characteristics and the nodular locations were compatible with an O. osleri respiratory tract infection.
Keywords: Chrysocyon brachyurus; maned wolf; Metastrongyloidea; Oslerus osleri; tracheobronchoscopy